First measurements of black hole accretion and radio-jet timescales in a young quasar at the edge of reionization - Rojas-Ruiz, Sofía; Momjian, Emmanuel; Davies, Frederick B.; Bañados Torres, Eduardo; Eilers, Anna-Christina; Bosman, Sarah; Vaidya, Bhargav; Carilli, Chris; Mazzucchelli, Chiara; Connor, Thomas; Khusanova, Yana (The astrophysical journal, 2025)
We present the first study dedicated to measuring the timescales for black hole accretion and jet launching in a quasar at the edge of reionization, PSO J352.4034-15.3373 at z = 5.832 ± 0.001. Previous work presented evidence of the strong radio synchrotron emission from the jet affecting the host galaxy's dust-dominated continuum emission at νrest = 683 GHz (νobs = 100 GHz), implying a break in the synchrotron spectrum. In this work, we present quasi-simultaneous observations at 1.5 GHz-42 GHz with the Karl G. Jansky Very Large Array, and derive a frequency break at GHz ( GHz). Modeling these observations, we calculate the jet spectral aging from the cooling of electrons to be tspec ∼ 580 yr. From this measurement, we approximate the dynamical age tdyn to be ∼2000 yr, implying a recent jet ejection. We compare the jet timescale to the quasar’s lifetime (tQ) that indicates the duration of the latest black hole accretion event and is derived from the proximity zone size in the rest-UV/optical spectrum. However, a ghostly damped Lyα system affects this measurement yielding an upper limit of tQ ≲ 104 yr, consistent with the jet lifetime and indicative of a young quasar. This suggests that the triggering of a UV-bright quasar phase may occur within comparable timescales as the launch of a relativistic radio jet. Therefore, we may be witnessing an early stage of black hole and jet interactions in a quasar during the first billion years of the Universe.
Gesehen am 20.10.2025